2011
DOI: 10.1037/a0023140
|View full text |Cite
|
Sign up to set email alerts
|

Overshadowing and associability change.

Abstract: Three appetitive Pavlovian conditioning experiments with rats examined the associability of stimuli A and B that had a history of compound conditioning (ABϩ), relative to stimuli X and Y that had a history of conditioning in isolation (Xϩ, Yϩ). Following this training, Experiment 1 revealed that conditioned responding was higher to X and Y than to A and B (overshadowing). In a subsequent AYϩ, AXϪ, BYϪ test discrimination, the AY/BY discrimination was solved more readily than the AY/AX discrimination. In Experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
18
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 40 publications
4
18
1
Order By: Relevance
“…This pattern of test discrimination is identical to that reported in Jones and Haselgrove (2011), and therefore supports the possibility that the compound exposure to A and B, as compared to the elemental exposure to X and Y, may have contributed to their results. The results of Experiment 1 are also consistent with the results of a latent inhibition experiment reported by Honey and Hall (1988).…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…This pattern of test discrimination is identical to that reported in Jones and Haselgrove (2011), and therefore supports the possibility that the compound exposure to A and B, as compared to the elemental exposure to X and Y, may have contributed to their results. The results of Experiment 1 are also consistent with the results of a latent inhibition experiment reported by Honey and Hall (1988).…”
Section: Resultssupporting
confidence: 84%
“…This result was again inconsistent with the idea that attention was less to A than to Y; if this were the case, the more salient Y should have taken better control over instrumental responding on R1 than had the less salient A. Jones and Haselgrove (2011) suggested that their results, while incompatible with Mackintosh's (1975) original model of attention and learning, could be explained by a more complex hybrid model proposed by Pearce and Mackintosh (2010). To avoid undue repetition, the details of this explanation will not be described fully here, but, in brief, the analysis is based on the idea that an algorithm that employs a total prediction error (Rescorla & Wagner, 1972) is used to update associative connections between the CS and the US and that an algorithm that employs an individual prediction error between each CS and the US (Bush & Mosteller, 1951) is used to update attention to a CS.…”
mentioning
confidence: 74%
See 3 more Smart Citations